2014
DOI: 10.3389/fpsyg.2014.01281
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying long-range correlations and 1/f patterns in a minimal experiment of social interaction

Abstract: In recent years, researchers in social cognition have found the “perceptual crossing paradigm” to be both a theoretical and practical advance toward meeting particular challenges. This paradigm has been used to analyze the type of interactive processes that emerge in minimal interactions and it has allowed progress toward understanding of the principles of social cognition processes. In this paper, we analyze whether some critical aspects of these interactions could not have been observed by previous studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 30 publications
8
24
0
Order By: Relevance
“…Bedia et al (2014) confirmed the multi-scale character of human–human interaction in a modified and constrained version of the PCE.…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Bedia et al (2014) confirmed the multi-scale character of human–human interaction in a modified and constrained version of the PCE.…”
Section: Introductionsupporting
confidence: 59%
“…In the present study a time-series approach to dyadic embodied social interaction was adopted as a response to the critical claim by Bedia et al (2014), who pointed out that the previous PCE analyses were limited to a single time-scale, failing to account for the whole dynamics of dyadic social interaction. Specifically, Bedia et al (2014) used to DFA and multifractal DFA to show that the fluctuations of such an interaction followed a power law distribution characteristic of 1/f β noise (with β≈1 ), as well as that this type of interaction could be considered as a multifractal system in which multiple scales were involved, meaning that more than one scaling exponents would be needed to fully characterize the dynamics of the system (Kantelhardt, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations